Physical and Mechanical Properties of Plywood Produced with Thermally Treated Pinus taeda Veneers - Ferreira, Bruno Santos [UNESP]; Arroyo, Felipe Nascimento; Kondo, Marcel Yuzo [UNESP]; Santos, Herisson Ferreira dos; Barreto, Rogério Lima; Dias, Alfredo Manuel Pereira Geraldes; Lahr, Francisco Antônio Rocco; Christoforo, André Luis; Campos, Cristiane Inácio de [UNESP] (MDPI, 2022)
Plywood is a structural composite mainly applied in construction. For this purpose, some sort of preservative treatment is recommended to increase its durability. One option of the available treatments is heat treatment, which promotes the modification of the wood properties. This treatment is carried out on the final product (plywood), because it can reduce strength if applied to the veneers. However, no study has proven such a reduction. Therefore, the aim of this work was to evaluate three different temperatures (160 °C, 180 °C and 200 °C) of the heat treatment on the veneer surface and on the physical properties (specific gravity, moisture content and swelling in thickness) and mechanical properties (MOE and MOR in static bending) of Pinus taeda plywood. A reduction was observed in the roughness of the veneer’s surfaces and the total extractives content changed, with a minimum value reached in the 160 °C treatment. The plywood specific gravity initially increased with the heat treatment and did not change at higher temperatures, moisture content reduced, and thickness swelling was not affected. There was no change in the mechanical properties of the plywood, evidencing that the veneer heat treatment does not prejudice mechanically the final product.
Keywords: bonding quality; chromated copper arsenate; heat treatment; mechanical properties; wood panels